Sumbangsih Eksistensi Kepemimpinan Tobara’ Terhadap Pembangunan Jemaat Di Lembang Siraun, Kecamatan Kalumpang, Kabupaten Mamuju, Provinsi Sulawasi Barat - Henri Sirangki; Darius (Institut Agama Kristen Negeri Toraja, 2022)
The purpose of this study was to determine the contribution of the existence of Tobara's leadership to the development of the congregation in Lembang Siraun, Kalumpang District, Mamuju Regency, West Sulawesi Province. Tobara' (customary leader) is a traditional leadership figure that exists in every Lembang (village) scattered in Kalumpang District. The existence of Tobara' in every lembang is to keep the adat alive. The contribution of the existence of Tobara's leadership to the development of the congregation in Lembang Siraun, Kalumpang District, Mamuju Regency, West Sulawesi Province is to create peace in Lembang, namely between the general public and church members. In addition, if there is a conflict that is difficult for the church to resolve, then Tobara'can resolve the conflict. The contribution of the existence of Tobara's leadership to the development of the congregation is to create peace in Lembang Siraun, it can even prevent conflicts that occur in the church and can create harmony. This study uses a qualitative-descriptive method that uses an observation and interview approach. Observations were carried out directly by researchers in Lembang Siraun. The purpose of the observation is to obtain information about the existence of Tobara' in Lembang Siraun. The researcher also conducted interviews with the main character, Tobara' as the leader in Lembang Siraun. In addition, researchers conducted interviews with members of the congregation in the GKSB church and even the community. Interviews conducted by researchers are unstructured interviews that ask questions freely. In this study, the results showed that the existence of Tobara's contributed to the development of the West Sulawesi Christian Church. Tobara' can cooperate with church leaders in creating harmony, so that the congregation's spirituality is stronger. Tujuan penelitian ini adalah untuk mengetahui sumbangsih eksistensi kepemimpinan Tobara’ (pemangku adat) terhadap pembangunan jemaat di Lembang Siraun, Kecamatan Kalumpang, Kabupaten Mamuju, Provinsi Sulawesi Barat. Tobara’ (pemangku adat) merupakan tokoh pemimpin adat yang ada dalam setiap Lembang (desa) yang tersebar dalam Kecamatan Kalumpang. Eksistensi Tobara’ di setiap lembang adalah untuk menjaga adat agar tetap eksis. Penelitian ini menggunakan metode kualitatif-deskriptif yang menggunakan pendekatan observasi dan wawancara. Observasi dilakukan langsung oleh peneliti dalam lembang siraun. Tujuan observasi adalah untuk mendapatkan informasi tentang eksistensi kepemimpinan Tobara’. Peneliti juga melakukan wawancara terhadap tokoh utama yakni Tobara’ sebagai pemimpin dalam Lembang Siraun dan tokoh masyarakat. Wawancara yang dilakukan peneliti adalah wawancara tidak terstruktur yang mengajukan pertanyaan secara bebas. Temuan-temuan dalam penelitian ini yakni; pertama, Sumbangsih eksistensi kepemimpinan Tobara’ terhadap pembangunan jemaat adalah menciptakan perdamaian dalam Lembang baik masyarakat yang ada di lembang tersebut maupun warga gereja. Kedua, keberadaan sebagai Tobara’ adalah untuk menyelesiakan konflik ketika ada persoalan yang sulit diselesaikan oleh gereja. Ketiga, keberadaan sebagai Tobara’ (pemangku adat) mampu menciptakan ketentraman, mencegah konflik yang terjadi, serta mampu menciptakan keharmonisan.